Urgensi Penerapan Smart Contract Sebagai System-Embedded Compliance Pada Pengawasan Fintech Syariah - Fitrawansah Fitrawansah; Sri Aisyah Yope; Evi Harviani (Maro: Jurnal Ekonomi Syariah dan Bisnis, 2026)
The rapid growth of the Islamic financial technology (fintech) industry in Indonesia faces serious challenges regarding Sharia compliance assurance due to the limitations of conventional supervision mechanisms. The current supervision system, which relies on manual post-transaction (post-facto) audits and sampling-based checks by the Sharia Supervisory Board (DPS), has proven inadequate in keeping pace with the volume and complexity of digital transactions. These weaknesses trigger various violations, ranging from fictitious murabahah practices without real assets to moral hazard risks caused by information asymmetry in profit-sharing contracts. This study aims to analyze the urgency of implementing smart contract technology as a solution to overcome this supervision gap. The method used is library research with a descriptive-analytical qualitative approach, examining regulations (DSN-MUI Fatwas and POJK) as well as prior scientific literature related to the weaknesses of the DPS and the characteristics of smart contracts. The analysis results indicate that smart contracts are deemed capable of functioning as a "Digital DPS" that automates Sharia parameters into algorithms. Unlike manual supervision, this system offers a real-time pre-transaction (ex-ante) validation mechanism that automatically rejects (auto-reject) any transaction failing to meet the valid conditions of the contract before funds are disbursed. In conclusion, the transition towards smart contract-based system-embedded compliance is deemed capable of maintaining the integrity of the fintech industry in the digital era.